Effect of Shear Reinforcement on Punching Shear Capacity of Reinforced Concrete Flat Plates. Issue 4 (December 2020) - Mohamed, Osama; Khattab, Rania
Abstract: Punching or two-way shear is a critical failure mode that must be accounted for in reinforced concrete (RC) slabs that are not supported by beams, known as flat plates. The often gravity-driven failure occurs around supporting columns may also be influenced by lateral forces. This paper presents the findings of a numerical study that evaluated the effect on punching shear strength of shear reinforcement bar diameter, and stirrups distribution length (L), measured from the face of the supporting column. The study was conducted on seven 3D nonlinear finite element models representing RC flat plates subjected to concentric vertical loads. Each of the seven models simulates the punching shear behaviour of interior slab-column connections with different shear reinforcement bar diameters and/or reinforcement distance from the face of the supporting column. Numerical investigation showed that increasing the stirrup diameter causes a significant increase in the ultimate two-way shear capacity. On the other hand, increasing the stirrups distribution length provides a moderate increase in the ultimate punching shear capacity. Furthermore, punching shear assessment using 3D finite element analyses were in good agreement with the mathematical models of the ACI-318-2019 building code.